Psychometric properties of the Providers Survey in the Brazilian context of mental health: a validation study - Lacerda, Mayara Karoline Silva; Vieira, Maria Aparecida; Marques, Fabrine Costa; Alves, Juliana Pereira; Pereira, Matheus Mendes; Carmo, Andreia Cristina Feitosa do; Costa, Mark Napoli; Caldeira, Antônio Prates; Sampaio, Cristina Andrade (São Paulo Medical Journal, 2025)
BACKGROUND: Precisely determining the aspects related to an instrument’s validity and reliability measures allows for greater assurance of the quality of the results. OBJECTIVES: To analyze the psychometric properties of The Providers Survey in the Brazilian context of mental health services. DESIGN AND SETTING: The instrument validation study was conducted in Montes Claros, Minas Gerais, Brazil. METHODS: The validation study was conducted using the Consensus-based Standards for the Selection of Health Measurement Instruments checklist to analyze its validity and reliability. RESULTS: A committee of expert judges performed content validation after which the Content Validity Index was calculated. Construct validation took place through Exploratory Factor Analysis using the Kaiser-Meyer-Olkin Test criterion and Bartlett’s Sphericity Test. Reliability was verified using test-retest reliability. The significance level adopted for the statistical tests was 5% (P < 0.05). The final instrument comprised 54 questions. The Content Validity Index was 97%. Exploratory Factor Analysis identified a Kaiser-Meyer-Olkin index of 0.901 and Bartlett’s Sphericity Test with P < 0.001. We obtained a Cronbach’s alpha coefficient of 0.95 and an intraclass correlation coefficient of 0.849. CONCLUSIONS: The Providers Survey, translated and adapted into Portuguese, was named the Work Assessment Instrument for the Recovery of Mental Health. It presented adequate psychometric properties for evaluating work-related practices for the recovery of psychosocial care network users.